2004
DOI: 10.1182/blood-2004-03-1140
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 uses novel mechanisms for yeast phagocytosis in macrophages

Abstract: The phagocytosis of pathogens is a critical event in host defense, not only for clearance of the invading microorganism, but also for the subsequent immune response. We have examined Dectin-1, a proinflammatory nonopsonic receptor for ␤-glucans, and show that it mediates the internalization of ␤-glucan-bearing ligands, including yeast particles. Although requiring tyrosine phosphorylation and the cytoplasmic immunoreceptor tyrosine-based activation motif (ITAM)-like motif, uptake mediated by Dectin-1 was diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
356
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 411 publications
(376 citation statements)
references
References 40 publications
17
356
0
3
Order By: Relevance
“…It is known that DC interact with yeasts essentially by the mannose-binding receptors CD206 [22,31] and DCspecific intercellular adhesion molecule-grabbing nonintegrin (DC-SIGN) [32,33], the b-glucan receptor dectin-1 [27,32,[34][35][36][37], and TLR2 [32,38,39]. Therefore, we analyzed Candida uptake in the presence of mannan, which binds both CD206 and DC-SIGN [40,41] and interferes with particle internalization by these receptors [42], or laminarin, a specific dectin-1 inhibitor [27,35,40,41,43]. Fig.…”
Section: Receptors Involved In C Albicans Uptakementioning
confidence: 99%
“…It is known that DC interact with yeasts essentially by the mannose-binding receptors CD206 [22,31] and DCspecific intercellular adhesion molecule-grabbing nonintegrin (DC-SIGN) [32,33], the b-glucan receptor dectin-1 [27,32,[34][35][36][37], and TLR2 [32,38,39]. Therefore, we analyzed Candida uptake in the presence of mannan, which binds both CD206 and DC-SIGN [40,41] and interferes with particle internalization by these receptors [42], or laminarin, a specific dectin-1 inhibitor [27,35,40,41,43]. Fig.…”
Section: Receptors Involved In C Albicans Uptakementioning
confidence: 99%
“…This inhibitor interferes with actin filament formation, showing that this process is crucial for the shaving reaction. Interestingly, however, none of the inhibitors that block specific signaling pathways important for phagocytosis (47) was able to inhibit shaving, showing that shaving and phagocytosis are mechanistically distinct. Finally, we found that a protease inhibitor mixture blocked shaving (Fig.…”
Section: Exploration Of Mechanismmentioning
confidence: 99%
“…However, shaving was not blocked by tyrosine kinase inhibitors known to block phagocytosis (Fig. 8A) (47). Phagocytosis is characterized by sequential phosphorylation of cellular proteins mediated by Src and Syk kinases (66), whereas simple endocytosis of small Ab-Ag complexes does not require tyrosine kinase action (23).…”
Section: Role Of Fc␥r In the Mechanism Of Shavingmentioning
confidence: 99%
See 2 more Smart Citations